POLITICAL PEOPLE OF THE USA - Karimova Robiyaxon; Abdurakhmanov Turakhon Saydullayevich (TADQIQOTLAR, 2025)
Annotation:This article provides a comprehensive overview of the key political figures in the United States, their roles, responsibilities, and influence on national and international  affairs.  It  examines  the  hierarchy  of  political  positions  in  the  U.S. government  and  highlights  prominent  individuals  who  have  shaped  the  political landscape  throughout  history.  The  article  also  explores  how  these  figures  impact policymaking, diplomacy, and the democratic process.